PENGARUH KUALITAS PELAYANAN DAN CUSTOMER EXPERIENCE TERHADAP KEPUASAN NASABAH PADA PT BANK CENTRAL ASIA, TBK DI CABANG KUTABUMI TANGERANG - Debora, Sylvianna; Marthadinata, Suryadi (Journal of Research and Publication Innovation, 2024)
The aim of this study is to investigate the Influence of Service Quality and Customer Experience on Customer Satisfaction at PT Bank Central Asia, Tbk Kutabumi Branch in Tangerang. The method used in this research is quantitative descriptive method with an associative approach. The sampling technique employed is probability sampling, using the Slovin's formula theory for sample selection. The analysis includes regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The research findings indicate that Service Quality (X1) and Customer Experience (X2) have a positive and significant influence on Customer Satisfaction (Y) with the regression equation Y = 0.040 + 0.296 (X1) + 0.295 (X2) + α. The coefficient of determination shows a combined influence of 63.6%. Partial hypothesis testing reveals that Service Quality (X1) with t-value > t-table (12.362 > 1.985), rejecting H0 and accepting H1, indicating a positive and significant influence of the independent variable Service Quality (X1) on Customer Satisfaction (Y). Similarly, Customer Experience (X2) with t-value > t-table (12.404 > 1.985) rejects H0 and accepts H2, indicating a positive and significant influence of the independent variable Customer Experience (X2) on Customer Satisfaction (Y).Simultaneous hypothesis testing between Service Quality (X1) and Customer Experience (X2) with F-value > F-table (84.017 > 3.090) rejects H0 and accepts H3, suggesting that Service Quality (X1) and Customer Experience (X2) together have a positive and significant influence on Customer Satisfaction (Y).